Development of Bamboo Mat - Wood Veneer Composites as Wood Substitute - Rajeev, B. N.; Naidu, M. V.; Rangaraju, T. S.; Zoolagud, S. S.; Aswathanarayana, B. S. (Indian Forester, 1998)
In view of decline in wood supplies, interest is growing on substituting wood. Results of the investigations carried out to substitute wood partially in plywood, a preferred panel due to its superior physical-mechanical strength properties, with bamboo mat are reported in this paper. Investigations have indicated that strength of a panel made by using plantation timber such as Grevillea robusta has been substantially enhanced when made in combination with bamboo mat. Physical-mechanical properties of such composite panels could be compared with the properties of special purpose plywood such as marine plywood and shuttering plywood. There is scope for further work to bring such thicker composite panels on par with special purpose plywoods like structural, marine, shuttering etc., by adopting optimum construction with veneers and bamboo mats. Manufacture of thicker panels using only bamboo mats was not an economical proposition hitherto. The present investigation has revealed that thicker panels can be manufactured economically using bamboo mats in combination with wood veneers. Details with respect to the manufacture of composite panels such as resin, resins and adhesive composition, application of adhesives, panel construction, hot pressing schedules are briefly described.